PENGUKURAN TINGKAT EFISIENSI BANK UMUM SYARIAH DI INDONESIA DAN DETERMINANNYA - Bisri Bisri (Universitas Bina Sarana Informatika, 2016)
This study examines the efficiency of Islamic banking and the determinant of its efficiency. This study using the DEA as a tool of bank efficiency analysis because of its the eminence to analyze the level of banking efficiency. Then proceed with an analysis fixed effects regression method (MET) to analyze the determinant factors of Islamic banking efficiency, that is capital structure, inflation and BI Rate. The results proved that based on the production approach, intermediation approach, and asset approaches the average level relative efficiency of Islamic Banking less than 100%. Then The panel data regression model proved that based on production approaches, capital structure variable effects Islamic Banks efficiency levels. Beside that the result also proved variable capital structure affect efficiency level of Islamic Banks by the intermediation approach. While the asset approach, proved variable capital structure, inflation and BI rate affect level of efficiency Islamic Banks. Meanwhile, simultaneously capital structure, inflation and BI rate affect Islamic bank efficiency based on production, intermediation and asset approach.Keywords: Efficiency, DEA (Data Envelopment Analysis) and regression panel.